Rohan at BlueOcean Tech - Vohra, Neharika, 1966-; Mendonca, Valerie; Sharma, Supriya (London : Indian Institute of Management, Ahmedabad, 2020)
Rohan Arora and Shantul Mukherjee co-founded the start-up BlueOcean Tech in June 2013, and both of them onboarded Niraj Bhardwaj as a co-founder. The equity of the start-up was split between Rohan and Shantul at 40% each, and Niraj owned the rest. In less than two years of the foundation, the start-up seemed to be doing well, especially in terms of technology and products, evident from the ability to land clients as well as garner media attention. They expanded the team to seven employees after a year. Rohan, the Chief Executive Officer (CEO), observed some of the team members arriving late to work, which resulted in delays in servicing clients. He felt it essential to address the issue of late arrivals by proposing punitive action against the defaulters. The attempts to make employees arrive on time backfired when Rohan confronted Niraj for being late to work one day. Niraj and Rohan had a heated argument, and Niraj sent Rohan his resignation by the end of the day, demanding his share of equity, which, in turn, threatened to jeopardize business development.The case highlights issues of managing people and teams in early-stage start-ups. The dilemma faced by the main protagonist is whether to let go of one of the co-founders.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Personnel management -- Case studies; Conflict management -- Case studies; Teams in the workplace -- Case studies